Cardiac Risk Assessment in Kidney Transplant Candidates: Clinical Usefulness of Different Guidelines - ÇİNÇİN, AHMET ALTUĞ; VELİOĞLU, ARZU; AŞICIOĞLU, EBRU; ARIKAN, HAZAL (ELSEVIER SCIENCE INC, 2019)
Although cardiovascular (CV) assessment is recommended to minimize perioperative risk in all potential kidney transplant recipients, the utility and reliability of various assessment methods are not well established. In this study, we investigated the CV evaluations and outcomes of standardized CV assessment protocols (Lisbon and American Society of Transplantation [AST]) in potential kidney transplant recipients. Data were analyzed for 266 end-stage renal disease patients (mean age 45.4 +/- 13 years, female-to-male ratio 126:140) accepted for kidney transplantation wait-listing. Patients were classified as low and high cardiac risk according to their first cardiac evaluation. Major cardiovascular events (CVEs) and deaths were recorded. At the end of follow-up (median 639 days), 72 (27.1%) patients underwent kidney transplantation. A total of 49 patients (18.4%) had CVEs and 42 (15.8%) patients died. Being over 45 years of age and having dialysis vintage over 1 year were found to be independent risk factors for CVEs. Forty-eight out of 60 high-risk patients evaluated with noninvasive tests had negative results. Twelve out of these 48 patients had a CVE in due course. Among 10 patients who underwent coronary angiography, 1 had a CVE and 1 died. The sensitivity and specificity of the AST guidelines (area under the curve = 0.647, P = .005, sensitivity 83%, specificity 54%) were higher than Lisbon. In conclusion, the predictive risk factors for CVEs were age over 45 years and dialysis vintage over a year. Our results also suggest that exercise electrocardiography and myocardial perfusion scintigraphy for cardiac evaluation are less sensitive in CVE prediction. We recommend clinicians to use the AST guidelines and to prioritize coronary angiography in pretransplant CV assessment.
Keywords: CORONARY-ARTERY-DISEASE; MYOCARDIAL-INFARCTION; RECIPIENTS; CARE